2019
DOI: 10.1016/j.jaci.2018.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of eosinophilic esophagitis in children with repaired congenital esophageal atresia

Abstract: Background: A high prevalence of eosinophilic esophagitis (EoE) has been preliminarily reported in patients after repair of esophageal atresia (EA), but the basis of this association is unknown Objectives: We aimed to (1) characterize the EoE transcriptome in patients with EA, (2) compare the EoE transcriptome in patients with EoE and EA with that in patients with EoE alone, and (3) identify transcripts that could predispose patients with EA to EoE. Methods: This single-center, population-based, retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
0
20
0
1
Order By: Relevance
“…It is now accepted that EoE is the result of a T-helper cell 2–type immune response in which eotaxin 3 and interleukins (IL) 4, 5, and 12 and 13 are upregulated (2729). The gene for eotaxin-3, which is a chemoattractant and activating factor for eosinophils, has been shown to be increased 53-fold above normal levels in patients with EoE (28, 30, 31). Both EA and EoE are polygenic conditions, and recently, Gorter et al postulated a possible genetic association between EA and EoE through mutations in the FOX gene cluster (6).…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…It is now accepted that EoE is the result of a T-helper cell 2–type immune response in which eotaxin 3 and interleukins (IL) 4, 5, and 12 and 13 are upregulated (2729). The gene for eotaxin-3, which is a chemoattractant and activating factor for eosinophils, has been shown to be increased 53-fold above normal levels in patients with EoE (28, 30, 31). Both EA and EoE are polygenic conditions, and recently, Gorter et al postulated a possible genetic association between EA and EoE through mutations in the FOX gene cluster (6).…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…This underscores the importance of being aware of the risk of EoE and performing endoscopies with sufficient numbers of biopsies at multiple levels, irrespective of the age in symptomatic EA patients. Also EA patients with EoE had a more-severe clinical phenotype, with higher incidence of dysphagia, episodes of food bolus impaction and strictures requiring dilation than in those with EoE alone without EA and EA patients without EoE, highlighting the importance of timely diagnosis and treatment of EoE in EA patients (31). This study found that 2 genes (ANO1 and CTNNAL1) were expressed more in EA patients with EoE than in EoE patients without EA.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…Krishnan et al 23 examined the relationship between EoE and congenital esophageal atresia. After finding a large increased risk for EoE in patients with surgically repaired esophageal atresia (364-fold enrichment), the investigators probed the related disease pathogenesis by subjecting the esophageal tissue to molecular profiling with the EoE Diagnostic Panel, a set of 94 transcripts associated with EoE.…”
Section: Eoementioning
confidence: 99%
“…Since the discovery of this disease, a vexing problem is the inability, either symptomatically or by objective testing, to definitively distinguish GERD from EoE. 7 Furthermore, other esophageal diseases such as achalasia 8 or esophageal astresia 9 have been described with mucosal eosinophilia with an unclear relationship to EoE. As a result, good clinical judgment is a mainstay in sorting out potentially complex interactions of these diseases in the face of possible EoE.…”
mentioning
confidence: 99%